28=2(3w-6)+2w

Simple and best practice solution for 28=2(3w-6)+2w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28=2(3w-6)+2w equation:



28=2(3w-6)+2w
We move all terms to the left:
28-(2(3w-6)+2w)=0
We calculate terms in parentheses: -(2(3w-6)+2w), so:
2(3w-6)+2w
We add all the numbers together, and all the variables
2w+2(3w-6)
We multiply parentheses
2w+6w-12
We add all the numbers together, and all the variables
8w-12
Back to the equation:
-(8w-12)
We get rid of parentheses
-8w+12+28=0
We add all the numbers together, and all the variables
-8w+40=0
We move all terms containing w to the left, all other terms to the right
-8w=-40
w=-40/-8
w=+5

See similar equations:

| 9+8x=8x-9 | | 0.60x+9=12 | | 6k^2+9k+0=0 | | (8-4i)(6+i)=0 | | 3/5x+9=12 | | 0.8x=21.27 | | 3x-6=-2x-46 | | -10+g+4-5=7g-5 | | 3,x,2,6;x= | | -107/18=2/3A+2-5a | | 49x+38=49x+33 | | -2(3k-8)-8=36+k | | 5x+(-2/5)=10 | | 49x+33=49x+33 | | 7x+6+8x-6=90 | | -3x-17=-17+3x | | 5x-2/3(x+5)=7x-x-1 | | -7x-3x+2=-10x+9 | | -(2x-19)=4x+1 | | 48+8x=23=7 | | 4x-8(5x+1)=6x+34 | | 5x+2x-3x-5=23 | | -3x-17=17(+3x) | | 4(2w+3)=12 | | 7^2+b^2=12^2 | | (7x-4)-(2x+6)=-2 | | 0=-25+5.3t-4.9t^2 | | 0=-25+5.3t-4.9t^2= | | 4(x+10)=2(2x-4) | | -5x-15=-5(x+3) | | -5/2u—5/3=-1/6u—7/2 | | 8x-(9x+4)=6x-46 |

Equations solver categories